Improvement of user interface for restaurant Point of Sale(POS) system from text based interface to graphical icon interface / Mohd Firdaus Mad Shah - Mad Shah, Mohd Firdaus (2006)
Graphical icon is one of the interaction styles in human computer interaction nowadays. Previous studies have shown that graphical icon help users when using a database system at the library in term of accuracy and completion time. This research is aimed to find out the advantages of using graphical icon and to evaluate the graphical icon that used in Restaurant Point of Sale (POS) System. The evaluation is done by comparing the uses of graphical icon and text based using Student's t-Test and by interviewing the participant.